A quick response and tribologically durable graphene heater for rapid heat cycle molding and its applications in injection molding. (25th February 2020) - Yang, Huaguang; Yilmaz, Galip; Han, Guebum; Eriten, Melih; Zhang, Zhi; Yu, Shengrui; Shi, Meinong; Yan, Hua; Yang, Weimin; Xie, Pengcheng; Turng, Lih-Sheng
Highlights: Outstanding performance graphene heater was prepared by one-step CVD method. The highest temperature provided by the graphene heater could exceed 300 °C. The tribologically durable graphene heater could be used in plastic molding industry. The graphene heater was utilized to improve LGFR PP's surface appearance. Abstract: A novel one-step approach was employed to achieve direct, high-strength graphene coating on a silicon wafer through chemical vapor deposition (CVD). The coated graphene on the silicon wafer was then assembled into a thin-film heater to realize rapid heat cycle molding (RHCM) with significantly enhanced thermal management and response. As soon as the applied power was turned on, the temperature rose immediately. The surface temperature of the graphene heater increased with the applied power and time, and the highest temperature exceeded 300 °C. The average heating rate reached 11.6 °C/s at an applied power of 360 W. Four-point temperature testing and temperature response during cyclic heating and cooling showed great temperature uniformity and stability. A tribology test was carried out to characterize the wear resistance of the graphene coating as a function of different coating times. As the coating time (graphene thickness) increased, the coefficient of friction (COF) for the coating decreased, and the wear resistance increased. The graphene heater with a 48 Ω surface resistance made by a 60 min coating time proved to be the best choice for RHCM with regard to the heating efficiency. The graphene heater was used in the RHCM of long-glass-fiber-reinforced (LGFR) PP composites to reduce the width and depth of the weld lines, decrease the floating fiber phenomenon, and improve the surface quality. The graphene heater also has great potential in other high-precision molding applications that require smooth surface, low molded-in residual stresses and birefringence, and superior replication of surface microstructures.